Interaction Analysis of a Plasmodium falciparum PHISTa-like Protein and PfEMP1 Proteins - Yang, Baoling; Wang, Xiaofeng; Jiang, Ning; Sang, Xiaoyu; Feng, Ying; Chen, Ran; Wang, Xinyi; Chen, Qijun (Frontiers in Microbiology, 2020)
Plasmodium falciparum extensively remodels host cells by translocating numerous proteins into the cytoplasm of red blood cells (RBCs) after invasion. Among these exported proteins, members of the Plasmodium helical interspersed subtelomeric (PHIST) family are crucial for host cell remodeling and host-parasite interactions, and thereby contribute to malaria pathogenesis. Herein, we explored the function of PF3D7_1372300, a member of the PHIST/PHISTa-like subfamily. PF3D7_1372300 was highly transcribed and expressed during the blood stage of P. falciparum, and distributed throughout RBCs, but most abundant at the erythrocyte membrane. Specific interaction of PF3D7_1372300 with the cytoplasmic tail of P. falciparum erythrocyte membrane protein 1 (PfEMP1) was revealed by immunofluorescence assay, in vitro intermolecular interaction assays. The interaction sites of PF3D7_1372300 with PfEMP1 ATS domain were found involved more than 30 amino acids (aa) at several positions. The findings deepen our understanding of host-parasite interactions and malaria pathogenesis.